2008
DOI: 10.1557/jmr.2008.0325
|View full text |Cite
|
Sign up to set email alerts
|

Shear deformation capability of different metallic glasses

Abstract: The mechanical properties of Zr52.5Ni14.6Al10Cu17.9Ti5 and Ti40Zr25Ni3Cu12Be20 metallic glasses were investigated under uniaxial compressive loading and small punch loading, respectively. The Zr-based metallic glass displays higher density of shear bands, larger critical shear offsets and higher energy absorbing capability than the Ti-based metallic glass under the small punch tests. A concept of critical shear offset is proposed to explain the difference in shear deformation abilities or plasticity of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…However, it is noted that the compressive plasticity of the Ti-based metallic glasses is near zero. [20] These results indicate that the brittle Ti-based metallic glass can also display a macroscopically high plasticity under the current SPT method with additional confinement, which must be highly related to the microscopically dense shear bands, and is discussed below.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…However, it is noted that the compressive plasticity of the Ti-based metallic glasses is near zero. [20] These results indicate that the brittle Ti-based metallic glass can also display a macroscopically high plasticity under the current SPT method with additional confinement, which must be highly related to the microscopically dense shear bands, and is discussed below.…”
mentioning
confidence: 87%
“…[17] Recently, the mechanical properties of metallic glasses under biaxial tensile loading were studied by the small punch test (SPT). [18][19][20] It was interesting to find that the metallic glasses could be controlled to create regularly arrayed, fine, multiple shear bands under the SPT, indicating that metallic glasses essentially have a good plastic-deformation capability and thus high ductility under suitable loading conditions. The findings showed that the initiation and propagation of shear bands in metallic glasses strongly depend on the stress state.…”
mentioning
confidence: 99%
See 3 more Smart Citations